Performance of encased single stone column in layered soil - Farah, Rowad Esameldin; Nalbanto?lu, Zalihe (Institute of Physics Publishing helen.craven@iop.org, 2020)
Stone columns were found to be effective, economical and widely-used ground improvement technique in soft grounds. It is important to understand the behavior of stone columns when they are installed in layered soils. This paper presents results from a series of small scale laboratory model tests carried out in unit cell tank to investigate the behavior of floating and end bearing stone columns in layered soils with and without encasement, consisting of loose sand overlying a soft soil. Tests were conducted with loading only the stone column area to estimate the limiting axial capacity of stone column. Laboratory tests were carried out on a column of 10 cm diameter surrounded by layered soil. Test results indicated that the bearing capacity of layered soil has been improved in all cases of stone column applications. The non- encased floating stone columns gave better results than non-encased end bearing stone column. The inclusion of geotextile encasement resulted in further improvement of layered soil and the encased floating stone column had superior bearing capacity improvement. © Published under licence by IOP Publishing Ltd.
5th International Conference on New Advances in Civil Engineering, ICNACE 2019 -- 2019-11-08 through 2019-11-10 -- Kyrenia -- 160101